2007
DOI: 10.1038/sj.bjp.0707313
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological enhancement of the endocannabinoid system in the nucleus accumbens shell stimulates food intake and increases c‐Fos expression in the hypothalamus

Abstract: Background and purpose: Evidence indicates that the endocannabinoid, 2-arachidonoylglycerol (2-AG), increases food intake when injected into the nucleus accumbens shell (NAcS), thereby potentially activating hypothalamic nuclei involved in food intake regulation. We aimed to evaluate potential orexigenic effects of the endocannabinoid anandamide and of AA5HT, a fatty acid amide hydrolase (FAAH) inhibitor, and OMDM-1, an inhibitor of anandamide uptake, injected in the NAcS, as well as the effect of these treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
5
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 53 publications
5
96
5
2
Order By: Relevance
“…Furthermore, behavioral experiments have shown that rimonabant bilaterally microinjected into the NAcS selectively decreased highly palatable food intake in an operant task (Guegan, et al, 2013). Our results confirm and extend the previous evidence that intra-accumbens administration of anandamide or 2-AG increase standard chow consumption (Soria-Gómez, et al, 2007;Kirkham, et al, 2002) by a behavioral-specific mechanism. Taking together these findings, it seems possible that cannabinoid receptors modulate feeding behavior simultaneously by two independent processes; the first one, homeostatic, characterized by affecting energy balance and motivational processes (hunger, appetite, satiety) (Cota, et al, 2003;Escartín-Pérez, et al, 2009); and the second one, hedonic, increasing the rewarding properties of food and its hedonically positive sensory properties (Di Patrizio & Simansky, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, behavioral experiments have shown that rimonabant bilaterally microinjected into the NAcS selectively decreased highly palatable food intake in an operant task (Guegan, et al, 2013). Our results confirm and extend the previous evidence that intra-accumbens administration of anandamide or 2-AG increase standard chow consumption (Soria-Gómez, et al, 2007;Kirkham, et al, 2002) by a behavioral-specific mechanism. Taking together these findings, it seems possible that cannabinoid receptors modulate feeding behavior simultaneously by two independent processes; the first one, homeostatic, characterized by affecting energy balance and motivational processes (hunger, appetite, satiety) (Cota, et al, 2003;Escartín-Pérez, et al, 2009); and the second one, hedonic, increasing the rewarding properties of food and its hedonically positive sensory properties (Di Patrizio & Simansky, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The endocannabinoid system has been implicated in reward-driven feeding (Matias, Cristino & Di Marzo, 2008), and interestingly cannabinoid receptor 1 (CB1R) KO mice are resistant to diet-induced obesity, indicating that energy dense foods require endocannabinoid signaling to generate obesity (Quarta, et al, 2010). The experimental evidence indicates that the acute activation of CB1R in the NAcS by administration of anandamide (Soria-Gómez, et al, 2007) or 2-AG (Kirkham, Williams, Fezza & Di Marzo, 2002) consistently stimulates chow intake.…”
Section: Introductionmentioning
confidence: 99%
“…Other neurotransmitter systems in NAc also modulate food consumption, motivation, and hedonic impact of food rewards including, endocannabinoids, and amino acids (Maldonado-Irizarry et al, 1995;Shinohara et al, 2009;Soria-Gomez et al, 2007), some of which might interact with opioid signals in NAc shell (Faure et al, 2010;Mahler et al, 2007). Here we extended our analyses to orexin and acetylcholine (ACh) systems in NAc that modulate intake and food-motivated behaviors (Pratt and Kelley, 2004;Pratt et al, 2007;Thorpe and Kotz, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…Apart from the aforementioned effects of CB 1 activation in the PBN, an important role is likely to be played by ECS in MCH-expressing neurons of the LH that also regulate the activity of the nucleus accumbens while receiving inhibitory control from this area through GABAergic neurons that are also controlled by CB 1 receptors. 9 Further evidence of the role of ECS in the neuronal circuits integrating the activity of the hypothalamus and NAcS came from a recent study by Soria-Gomez et al 44 The orexigenic effects of (1) anandamide, (2) a FAAH inhibitor and (3) an inhibitor of anandamide cellular uptake, injected into NAcS, were evaluated parallel to their activation of cFos in various hypothalamic nuclei, including the LH. The results indicated that all the treatments stimulate food intake during 4 h post-injection, whereas also increasing cFos immunoreactivity in all hypothalamic nuclei analysed, in a way sensitive to CB 1 antagonism.…”
Section: Brief Introduction To the Endocannabinoid Systemmentioning
confidence: 99%